Time use of mothers and fathers in hard times and better times: The US business cycle of 2003-2010 - Günseli Berik; Ebru Kongar (The University of Utah, Department of Economics, 2011)
The U.S. economic crisis and recession of 2007-2009 accelerated the convergence of women's and men's employment rates as men experienced disproportionate job losses and women's entry into the labor force gathered pace. Using the American Time Use Survey (ATUS) data for 2003-2010, this study examines whether the narrowing gap in paid work over this period was mirrored in unpaid work, personal care and leisure time. We find that the gender gap in unpaid work followed a U-pattern, narrowing during the recession but widening afterwards. Through segregation analysis we trace this U-pattern to the slow erosion of gender segregation in housework and through a standard decomposition analysis of time use by employment status we show that this pattern was mainly driven by movement towards gender equitable unpaid hours of women and men with the same employment status. In addition, over the business cycle gender inequality in leisure time increased.
Keywords: D13; J16; J22; J64; 330; Economics of Gender; Unemployment; Time Use; Economic Crises